"Performance Accelerators" push the frontiers of CFO leadership. Issue 3 (13th May 2014) - Fuessler, Bill
Abstract : Purpose: – Through interviews last year with 576 CFOs to find out how they're contributing to the revenue, growth and foresight of the enterprises they represent, IBM researchers sought to identify the best practices of leading companies. Design/methodology/approach: – IBM researchers identified a cohort of companies with outstanding finance units they called Value Integrators, organizations that were more effective than their peers in almost every area assessed. The finance units were especially good at measuring and monitoring business performance, managing risk and generating predictive insights. Findings: – A subset of this group of successful firms far outperformed the rest. The researchers dubbed these superstars Performance Accelerators because they've mastered their core duties so thoroughly that they've taken a leap ahead of every other kind of finance organization. Practical implications: – The Performance Accelerators' particular blend of skills equipped them to help their companies make smarter decisions. Originality/value: – Performance Accelerators exert more influence on the enterprises they serve, and make a bigger contribution to performance than any other kind of finance organization. And they do so because they are particularly adept at generating deep insights that can be used to stimulate profitable growth.